KEMAMPUAN INFEKSIISOLAT Beauvetia sp. PADA STADIA LARVA ULAT Etionata thrax L - M. Rahmansyah; Erniwati Erniwati (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Tintomophatogemcfungus is isolated from an infected pupae ofH. thrax -L (Hesperiidae: Lepidoptera).The fungus 3 is cultured and determined as Beauveria sp.Conidia suspension of the fungi (7.6x10 conidia/ml) use as inoculant and reinoculated to five of difference larval stages.The larvae were cultured in the laboratory.The infected larvae become weak and finally died at ten days after inoculation.It is highly indication that the fungi may be potentially applicable as biocontrol agent for the insect.The fungus attack the E. thrax since the beginning of the larvae stage.